Scenarios of developing private brands for food products - Raluca Andreea Ion; Adrian Laurentiu Ariciu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Private brands are those manufactured or provided by one company for offer under another company's brand. They are often positioned as lower-price alternatives to national brands, and they are helping retailers to build sustainable relationships with their customers. The objective of this research is to identify the main directions of developing private brands for food products. Pursuing this, a documentary study was carried out, analyzing the situation of using private brands on different markets around the world. Research findings showed that private branding strategies differentiate themselves depending on the type of market: developed markets and emerging markets. In developed markets, there are great opportunities for development of premium segments, with top quality products and higher price, which gives the chance for higher differentiation of retailers and increased loyalty. In emerging markets, private label products have great potential, growing together with retail modernization and consolidation. These results are useful for retailers in their efforts to decide strategies for their private brands.
Keywords: 330; Private brands; food retail; emerging markets; premium products